Optimization of Distributed Generation in Radial Distribution Network for Active Power Loss Minimization using Jellyfish Search Optimizer Algorithm - Ranga, Jarabala; Y, Thiagarajan; D, Kesavan; Deglus, Jovin; Reddy, Sibbala Bhargava; Palanisamy, Rajakumar; R. A., Priya (International Journal of Electrical and Computer Engineering Systems, 2024)
The inclusion of distributed generation (DG) units in the distribution network (DN) effectively cuts down the power losses (PL) and strengthens the voltage profile (VP). This paper examines the effect of allocating different distributed generation (DG) in radial distribution networks (RDN) through an implementation of an optimization technique using a recently introduced bio- inspired algorithm known as a jellyfish search optimizer (JSO). Unlike the other optimization algorithms, the JSO algorithm evades the local optimal trap and reaches the optimal solution in less time. The DG position(s) and size(s) are optimized for active power loss (APL) minimization with respect to several constraints. The effectiveness and robustness of the proposed optimization technique using JSO algorithm is investigated on a balanced IEEE RDNs with 33, 69 and 118-buses. The simulation outcomes are obtained for different types (type I, II and III) of DG placement. Additionally, a comprehensive comparative study has been performed for the JSO and other algorithms. The comparison exemplifies that the proposed JSO optimization approach produces a better optimal solution with steady convergence than other techniques reported in the literature. Also, the simulation findings show the potentiality of JSO optimization method for solving complex optimization problems.